Zespół agroturystyczny w Drzonkowie, jako dyskurs nad znaczeniem tradycji miejsca = Agrotourimo with equestrian center in Drzonków, as a discours on land tradition - Kleszcz, Justyna; Kozłowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the issue of architecture as a form of knowledge transition of cultural continuity of a certain area basing on the example of a project: "Agrotourismo with equestrian center in Drzonków". The study was devoted to the design of agrotouristic hub with an equestrian center for 14 horses, at the site of a former equestrian complex, in a place which has recently become a part of Zielona Góra.
Keywords: ośrodek jeździecki; Drzonków; stajnia; pensjonat; budownictwo wiejskie; horse riding center; stables; riding school; agroturismo